Mechanisms of FLASH effect - Lin, Binwei; Huang, Dan; Gao, Feng; Yang, Yiwei; Wu, Dai; Zhang, Yu; Feng, Gang; Dai, Tangzhi; Du, Xiaobo (Frontiers in Oncology, 2022)
FLASH radiotherapy (FLASH-RT) is a novel radiotherapy technology defined as ultra-high dose rate (≥ 40 Gy/s) radiotherapy. The biological effects of FLASH-RT include two aspects: first, compared with conventional dose rate radiotherapy, FLASH-RT can reduce radiation-induced damage in healthy tissue, and second, FLASH-RT can retain antitumor effectiveness. Current research shows that mechanisms of the biological effects of FLASH-RT are related to oxygen. However, due to the short time of FLASH-RT, evidences related to the mechanisms are indirect, due to which the exact mechanisms of the biological effects of FLASH-RT are not completely clear and some are even contradictory. This review focuses on the mechanisms of the biological effects of FLASH-RT and proposes future research directions.